Optimized CorT Total to compare Scheimpflug vs dual Scheimpflug/Placido imaging devices. Issue 2 (February 2021) - Ferguson, Tanner J.; Piccinini, Andre L.; Thulasi, Praneetha; Ong, James K.Y.; Stamatelatos, George; Alpins, Noel; Randleman, J. Bradley
Abstract : Using optimized CorT Total as a benchmark, the performance of TCP measures from the dual Scheimpflug/Placido and Scheimpflug has improved with software changes. Abstract : Purpose: To compare the manufacturer-provided measures of total corneal power (TCP) generated by Scheimpflug and dual Scheimpflug/Placido imaging compared with corneal topographic astigmatism calculated on the basis of measured TCP data (CorT Total). Setting: Emory University, Atlanta, Georgia, USA. Design: Retrospective case series. Methods: TCP values were exported from virgin 209 eyes that underwent imaging with both the Scheimpflug (Pentacam HR) and dual Scheimpflug–Placido (Galilei G4) imaging devices to compute an optimized CorT Total. The standard deviation of the ocular residual astigmatism (ORAsd), which serves as a value describing the vectoral difference between the corneal astigmatism measure and manifest refractive cylinder at the corneal plane, was evaluated for all eyes to compare manufacturer-provided measurements vs the optimized CorT Total. Results: The Scheimpflug CorT Total had the lowest ORAsd (0.306 diopter [D]; spherical equivalent [SE] 0.018) of all the parameters evaluated, although the difference was not statistically significant ( P = .22) from the dual Scheimpflug/Placido CorT Total (0.32 2 D; SE 0.017). For the Scheimpflug device, the CorT Total had a statistically significant lower ( P < .05) ORAsd in comparison to the best measure on the device (total corneal refractive power apex zone 2 mm: 0.324 D; SE 0.021). For dual Scheimpflug/Placido measurements, the CorT Total had the lowest ORAsd (0.322 D; SE 0.017), but the difference was not statistically significant ( P = .43) from the lowest manufacturer-provided measure (TCP 2). Conclusions: CorT Total generated with the Scheimpflug device corresponded better with the manifest refractive cylinder than all measures of total corneal astigmatism calculated by the software from both the Scheimpflug and the dual Scheimpflug/Placido devices.